Root Cause of Indian Startups’ Failure: An Empirical Study: Challenges and Opportunities for Indian Startups in Delhi and NCR (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In order to achieve the target of 5 trillion economy, India needs to exploit its existing resources and to develop entrepreneurs mainly in small scale sector. We are a growing economy which is based on agriculture followed by manufacturing and service sector. In last decade the contribution of manufacturing and service sector in Indian economy is growing at a faster rate. Due to many policies framed by the government new entrepreneurs are coming up with new business ideas. The culture of startups is developing in India. The young generation prefers to start their own business rather than joining existing companies. Often these new ideas face financial difficulties mainly during the startup phase. A big number of SMEs are in scarcity of funds, they have yet to tap into the funds provided by the banks. Only a small portion of SMEs thus far have successfully received this funding and this big gap poses a question mark and triggers the need to conduct a study. Though there are a number of programs offered by the government but due to the red tapes, various formalities and the rigidity of the procedures, it hampers the smooth success of the programs. In the study the responses are collected from 310 entrepreneurs in the Delhi and NCR area, who are in the process of expanding their new startups.